Factors Affecting Toddlers'Development In Pamekasan Regency: Factors Affecting Toddlers'Development In Pamekasan Regency - Nur Jayanti; Uliyatul Laili; Rohemah Rohemah (Universitas Nahdlatul Ulama Surabaya, 2021)
Toddlers require basic needs – stimulation, love, and care – in the process of growth and development. Parents, especially mothers, are the most important factors in performing these three tasks: honing, loving, and fostering. The mother's physical and psychological conditions, including the mother's age at marriage, education, and stimulation, will impact children's development. This study aims to determine the factors that influence toddlers' development in the Pamekasan Regency. The research method used was descriptive-analytic, with a retrospective design. This study consisted of 110 mothers with toddlers by fixed exposure sampling in Waru, Batu Marmar, and Pasen Public Health Center. The dependent variable was the toddlers' development. The independent variables were the mother's age at marriage, family income, stimulation, mother's LILA during pregnancy, and birth weight. The analysis used the path analysis method. The results showed that the toddlers' development was influenced by the mother's age at marriage (b = 0.07, SE = 0.02, p = 0.001), family stimulation (b = 0.02, SE = 0.01, p = <0.001) and birth weight (b = 0.00, SE = 0.00, p = 0.373). This study concludes that maternal marriage age, family stimulation, and birth weight affect toddlers' development.